UJI VALIDITAS DAN RELIABILITAS KUESIONER INTENSI ORANG AWAM TERHADAP TINDAKAN RESUSITASI JANTUNG PARU - Fitri, Eka Yulia (JURNAL KESEHATAN INDRA HUSADA, 2024)
This study aims to measure the accuracy and reliability of the lay people's intention toward cardiopulmonary resuscitation questionnaire. It consists of 7 questions in case scenario with two answer choices. The validity testing of each question uses Pearson product-moment correlation and the internal consistency of the questionnaire uses Cronbach's alpha. A total of 34 lay people completed the questionnaire. The characteristics of the respondents were female (97,06%), the average knowledge score was 14,2 (±SD 1,47), the average attitude score was 17,9 (± SD 1,79), and 100% never performed cardiopulmonary resuscitation on cardiac arrest victims. The results of the analysis of 7 questions have a correlation coefficient of more than r-table (0,339; CI=95%) and have an internal consistency of α=0,871 (CI=95%). The questionnaire has accurate validity and consistent reliability. Questionnaires is valid and reliable for measuring lay people's intentions toward cardiopulmonary resuscitation.